Systematic review of the psychometric properties of patient-reported outcome measures for foot and ankle in rheumatoid arthritis - Ortega-Ávila, Ana Belén; Gijón-Noguerón, Gabriel; Cervera-Garvi, Pablo; Nester, Christopher; Ramos Petersen, Laura (My University, 2019)
Background Foot problems and pain are common in patients with rheumatoid arthritis. Patient-reported outcome measures provide a standardized method of capturing patients’ perspectives of their functional status and wellbeing. There are many instruments specific to people with feet affected by rheumatoid arthritis but knowledge of their psychometric validation or methodological quality is lacking Objectives To identify patient-reported outcome measures specific to the foot and ankle and rheumatoid arthritis and investigate their methodological quality and psychometric properties Design Systematic review. Data source : A search was conducted for psychometric or validation studies on patient-reported outcomes in Rheumatoid Arthritis published in different languages, by examining the Pubmed; Scopus, CINAHL; PEDro and Google Scholar databases. Review methods . The systematic review performed was based on the following inclusion criteria: psychometric or clinimetric validation studies on patient-reported outcomes specific to the foot and ankle that included patients with Rheumatoid arthritis. Two authors independently assessed the quality of the studies and extracted datas Results Of the initial 431 studies, fourteen instruments met the inclusion criteria. Significant methodological flaws were detected in most with only SEFAS met the COSMIN quality criteria. Conclusion SEFAS had the best quality and was ranked most appropriate for use with patients living with Rheumatoid Arthritis
Keywords: Artritis reumatoide; Pie; Tobillo; Cuestionarios